Children Picture-Book Series on Exploring the Causes of Low Self-Esteem Issues in Children and the Positive Effects after Overcoming Them - Graciela Adelia; Stefanny Irawan (Kata Kita: Journal of Language, Literature, and Teaching, 2020)
This paper discusses creating children picture-book stories which highlight the issue of self-esteem in children, particularly exploring the causes of low self-esteem in children as well as what children get after regaining their self-esteem. Serving as the theoretical framework are Erik Erikson’s Psychosocial Development, the concept of Praise Paradox, Body Image, and Colorism. In the first and second story, the main characters have low self-esteem because they feel unappreciated, and they later feel more loved and happier after overcoming their issues. In the third story, the main character has low self-esteem because she keeps receiving the wrong type of praise but later becomes calmer after overcoming her issue. The main characters in the fourth and fifth story have low self-esteem because of their appearances, but they will later be more confident and secure after overcoming their issues.Keywords: Children Picture-Books, Self-Esteem, Psychosocial Development, Praise Paradox, Body Image, Colorism